Frakturen des Processus posterior tali - Kammerer, K. P.; Biedert, R. M. (Sport-Orthopädie - Sport-Traumatologie, 2011)
Ankle sprains are common injuries in sports. Fractures of the posterior process of the talus are rare and might be overseen especially when they are not dislocated. They might be interpreted as ankle sprains and accordingly treated in a wrong way. In both cases patients suffer from chronic pain and dysfunction. To get the correct diagnosis it is essential to know the trauma mechanism and by this to get the appropriate radiologic examination. The radiologic differential diagnosis of a habitual Os trigonum and a pathologic finding of a fractured posterior process of the talus leads to the correct diagnosis and thus to the necessary therapy. It avoids a prolonged healing process.